Organizational Justice and Academic Ethics in Educational Conflict Management - Aerin Regina Putri; Mundzier Mohammad Mustarilamada (Journal of Strategy and Transformation in Educational Management, 2026)
Conflict is an inseparable phenomenon from the dynamics of educational organizations, considering the interaction between individuals with diverse backgrounds, interests, and roles. Conflicts that are not managed appropriately have the potential to disrupt the academic climate, reduce the quality of learning, and weaken trust in educational institutions. In this context, organizational fairness and academic ethics are important cornerstones in educational conflict management. Organizational justice includes procedural, distributive, and interactional fairness that influences the perception of academic citizens of institutional policies and decisions. Meanwhile, academic ethics serves as a moral guideline that directs professional behavior, integrity, and responsibility of the entire academic community.